Representasi Urgensi Pendidikan Seksual Remaja Studi Analisis Semiotika Pada Series “Little Mom” - Siti Khoiriyah Firdayati (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2023)
It is important to mention sexual education to women ever since the dawn of time. An adult and a child are more receptive to sexual information that is salient, yet it is possible that they are less aware of how detrimental it is to their mental health. A person's mental health has a critical role in their ability to succeed in life, carry out productive activities, adjust to various environmental changes, and resolve any discrepancies. The purpose of this study is to clarify the series Little Moms' depictions of sexual education. This study makes use of quantitative desk research methodology. The methodology for the study makes use of Roland Barthes' semiotics analysis, in which significant connections are made between denotation, cosmology, and mitology. The subjects of this study are Naura and Yuda. The focus of this study is on understanding the consequences of studying sex and engaging in sexual activity as shown in sexually explicit series, dialogue, and characters. Data collection methods include observation, literature study, and documentation. The series "Little Mom" is directed by director Guntur Soehardjanto. This series shows the important role of parents in communicating information about sex to their children, the wrong understanding of sex can lead to premarital sex. The results of this study indicate that there are depictions of sex education in films that affect mental health.